General population normative data for the EORTC QLQ-C30 health-related quality of life questionnaire based on 15,386 persons across 13 European countries, Canada and the Unites States - Nolte, S.; Liegl, G.; Petersen, M.A.; Aaronson, N.K.; Costantini, A.; Fayers, P.M.; Groenvold, M.; Holzner, B.; Johnson, C.D.; Kemmler, G.; Tomaszewski, K.A.; Waldmann, A.; et al. (European journal of cancer (1990), 2019)
The European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 health-related quality of life questionnaire is one of the most widely used cancer-specific health-related quality of life questionnaires worldwide. General population norm data can facilitate the interpretation of QLQ-C30 data obtained from cancer patients. This study aimed at systematically collecting norm data from the general population to develop European QLQ-C30 norm scores and to generate comparable norm data for individual countries in Europe and North America. We collected QLQ-C30 data from the general population across 11 European Union (EU) countries, Russia, Turkey, Canada and United States (n ≥ 1000/country). Representative samples were stratified by sex and age groups (18–39, 40–49, 50–59, 60–69 and ≥ 70 years). After applying weights based on the United Nations population distribution statistics, we calculated QLQ-C30 domain scores to generate a ‘European QLQ-C30 Norm’ based on the EU countries. Further, we calculated QLQ-C30 norm scores for all 15 individual countries. A total of 15,386 respondents completed the online survey. For the EU sample, most QLQ-C30 domains showed differences by sex/age, with men scoring somewhat better health than women, while age effects varied across domains. Substantially larger differences were seen in inter-country comparisons, with Austrian and Dutch respondents reporting consistently better health compared with British and Polish respondents. This study is the first to systematically collect EORTC QLQ-C30 general population norm data across Europe and North America applying a consistent data collection method across 15 countries. These new norm data facilitate valid intra-country as well as inter-country comparisons and QLQ-C30 score interpretation. •Updated general population norm data for EORTC QLQ-C 30 based on 15,386 persons across 13 European countries, Canada, and USA.•Study strength: all individual country QLQ-C30 norm data collected based on a common sampling strategy and survey design.•New normative data facilitate valid intracountry and especially intercountry comparisons and QLQ-C30 score interpretation.